Early biliary decompression versus conservative treatment in acute biliary pancreatitis (APEC trial): study protocol for a randomized controlled trial. Issue 1 (December 2016) - Schepers, Nicolien; Bakker, Olaf; Besselink, Marc; Bollen, Thomas; Dijkgraaf, Marcel; van Eijck, Casper; Fockens, Paul; van Geenen, Erwin; van Grinsven, Janneke; Hallensleben, Nora; Hansen, Bettina; van Santvoort, Hjalmar; et al.
Abstract Background Acute pancreatitis is mostly caused by gallstones or sludge. Early decompression of the biliary tree by endoscopic retrograde cholangiography (ERC) with sphincterotomy may improve outcome in these patients. Whereas current guidelines recommend early ERC in patients with concomitant cholangitis, early ERC is not recommended in patients with mild biliary pancreatitis. Evidence on the role of routine early ERC with endoscopic sphincterotomy in patients without cholangitis but with biliary pancreatitis at high risk for complications is lacking. We hypothesize that early ERC with sphincterotomy improves outcome in these patients. Methods/Design The APEC trial is a randomized controlled, parallel group, superiority multicenter trial. Within 24 hours after presentation to the emergency department, patients with biliary pancreatitis without cholangitis and at high risk for complications, based on an Acute Physiology and Chronic Health Evaluation (APACHE-II) score of 8 or greater, Modified Glasgow score of 3 or greater, or serum C-reactive protein above 150 mg/L, will be randomized. In 27 hospitals of the Dutch Pancreatitis Study Group, 232 patients will be allocated to early ERC with sphincterotomy or to conservative treatment. The primary endpoint is a composite of major complications (that is, organ failure, pancreatic necrosis, pneumonia, bacteremia, cholangitis, pancreatic endocrine, or exocrine insufficiency) or death within 180 days after randomization. Secondary endpoints include ERC-related complications, infected necrotizing pancreatitis, length of hospital stay and an economical evaluation. Discussion The APEC trial investigates whether an early ERC with sphincterotomy reduces the composite endpoint of major complications or death compared with conservative treatment in patients with biliary pancreatitis at high risk of complications. Trial registration Current Controlled TrialsISRCTN97372133 (date registration: 17-12-2012)